CTCF variants in 31 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, N.; Blyth, M.; Prescott, K.; Bouman, A. M.; Brilstra, E. H.; Caliebe, A.; Ibitoye, R.; Chang, V. Y.; Gupta, A.; Le Guyader, G.; Jamra, R. A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2021-10-18

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L.; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genetics in Medicine, 2019)
Purpose: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). Methods: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. Results: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. Conclusion: We significantly broaden the mutational and clinical spectrum of CTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.
Keywords: chromatin organization; CTCF; Drosophila melanogaster; intellectual disability; neurodevelopmental disorders

De novo missense variants in RHOBTB2 cause a developmental and epileptic encephalopathy in humans, and altered levels cause neurological defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, A.; Bok, L. A.; Cho, M. T.; Crawford, H. P.; Dubbs, H.; Douglas, G.; Jobling, R.; Johnson, D.; Krock, B.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Missense Variants in RHOBTB2 Cause a Developmental and Epileptic Encephalopathy in Humans, and Altered Levels Cause Neurological Defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, Annick; Bok, Levinus A.; Cho, Megan T.; Crawford, Heather P.; Dubbs, Holly; Douglas, Ganka; Jobling, Rebekah; Johnson, Diana; Krock, Bryan; et al. (American Journal of Human Genetics, 2018)
Although the role of typical Rho GTPases and other Rho-linked proteins in synaptic plasticity and cognitive function and dysfunction is widely acknowledged, the role of atypical Rho GTPases (such as RHOBTB2) in neurodevelopment has barely been characterized. We have now identified de novo missense variants clustering in the BTB-domain-encoding region of RHOBTB2 in ten individuals with a similar phenotype, including early-onset epilepsy, severe intellectual disability, postnatal microcephaly, and movement disorders. Three of the variants were recurrent. Upon transfection of HEK293 cells, we found that mutant RHOBTB2 was more abundant than the wild-type, most likely because of impaired degradation in the proteasome. Similarly, elevated amounts of the Drosophila ortholog RhoBTB in vivo were associated with seizure susceptibility and severe locomotor defects. Knockdown of RhoBTB in the Drosophila dendritic arborization neurons resulted in a decreased number of dendrites, thus suggesting a role of RhoBTB in dendritic development. We have established missense variants in the BTB-domain-encoding region of RHOBTB2 as causative for a developmental and epileptic encephalopathy and have elucidated the role of atypical Rho GTPase RhoBTB in Drosophila neurological function and possibly dendrite development.
EVALuna2:33715